Parents’ Attitudes towards Their Children’s Bilingualism and Cultural Identity in International Schools in Egypt - Aboulfetouh, Mona (AUC Knowledge Fountain, 2011)
This study examines Egyptian parents' attitudes towards their children's bilingualism in the context of English-medium international schools in Egypt. It also aims at comparing their past aspirations and motives to choose international schools and their current attitudes towards their children's school and educational experience. Research has shown that learners' attitudes towards the second language affect their language development. In addition, parents play a vital role in influencing their children's academic progress and attitudes towards their first language. Therefore, examining parents' opinions and attitudes towards their children's educational system and language learning is important to understand how these attitudes may influence their choices and home practices. The present study was conducted with the participation of parents of senior English-medium international school students in Egypt. In this study, 131 parents completed a survey; of those ten parents volunteered to be interviewed. Data has been analyzed qualitatively and descriptive statistics have been used to report findings. The findings confirmed the instrumental role of English in Egyptian society and parents' aspirations for their children to receive quality education and to find a good job in the future. Other motives for sending children to international schools have been found including the higher-socioeconomic level of students in international schools, acquiring a native-like accent and the highly qualified teachers hired in international schools. Parents discussed their former experiences that influenced their choice of the school, the skills their children develop in international schools and the fact that the other school systems in Egypt are deteriorating. In addition, the results revealed that parents believe that relatively little attention is given to Arabic by parents and even by the school. Some participants depend on the assistance of a private tutor or a sheikh to teach Arabic to their children. Other parents believe that English language is more important than Arabic nowadays for the academic and professional success of their children. The study can also be extended in the future to include children's attitudes and examine school curricula.